Social demographic aspects and self-referred health conditions of men attending a health care unit - Raissa de Oliveira Martins Cabacinha; Christian Dias Cabacinha; Daniel Silva Moraes; Henrique Andrade Barbosa; Lucinéia de Pinho (Rev Rene)
This study aimed at characterizing social demographic aspects and health conditions of men attending a Primary Family Health Care unit in Montes Claros, MG, Brazil, correlating these variables with health self-perception and identifying men’s difficulty in using the health service. 115 adult men were interviewed who had attended the service in April and May, 2013. Most of them had completed high school, were married and adopted healthy practices, although they consumed alcoholic beverages. The main complaint regarding the health service was the long waiting time for attendance. The main factors that contributed for negative self-perception of health were: being married, suffering from chronic diseases and having low education; whereas those that contributed to the positive self-perception of health were: being young, being employed and not making regular use of medication (p<0.05). Those findings can subsidize policies to prevent diseases in promoting men’s health.